The Role Of Islamic Religious Education In The Formation Of Adolescent Character - Nurhaliza, Siti; Chairani, Chairani; Aditya, Fiqri (Educate: Jurnal Ilmu Pendidikan dan Pengajaran, 2024)
This article will discuss the role of Islamic religious education in schools in forming the character of teenagers. Islamic Religious Education (PAI) is one of the most important pillars of character education. Character education will grow well if it starts from instilling a religious spirit in children, therefore PAI material in schools is one of the supports for character education. Through PAI learning, students are taught aqidah as the basis of their religion, taught the Koran and hadith as a guide to life, taught fiqh as legal guidelines in worship, taught Islamic history as a living example, and taught morals as a guide to human behavior whether in the category of good or bad. bad. Therefore, the main goal of PAI learning is the formation of personality in students which is reflected in their behavior and thought patterns in everyday life. Apart from that, the success of PAI learning at school is also determined by the application of appropriate learning methods.